Impact of Risks Due to Exposure to Hydrogen Sulfide (H2S) on Communities Around the Medang Prabumulih River TPA - Firdaus, Qonita Rizqina; Arista Putri, Dini; Sunarsih, Elvi; Oktivaningrum, Rafika (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2023)
Sungai Medang Landfill in Prabumulih City manages waste through the sanitary landfill method, though not optimally. Waste undergoes anaerobic decay by microorganisms, producing hydrogen sulfide (H2S) gas. Low concentrations of H2S can irritate the eyes, nose, or throat. This study aimed to analyze the environmental health risks of H2S exposure to communities around the Medang Prabumulih River landfill. The Environmental Health Risk Analysis (EHRA) method with a deterministic approach was used. The study sampled 92 people living within a radius of 250 meters and ±500 meters, using purposive sampling techniques. Results showed the highest concentration of H2S at 0.0015 μg/m3 and the lowest at 0.0001 μg/m3. The average intake value (real time) was 0.00053 μg/m3, with a risk level of 0.267 RQ (<1). These results indicate that the current risk level due to H2S exposure is safe and does not pose non-carcinogenic health risks. However, future increases in H2S concentrations may occur due to the rising amount of waste from increased population and urbanization. It is recommended to install air purifiers in homes and plant barrier plants like Liriope spicata (lilyturf/monkey grass) around residences to reduce odors from the landfill.